Health related quality of life of HIV/AIDS patients on highly active anti-retroviral therapy at a university referral hospital in Ethiopia - Abdrrahman Shemsu Surur; Fitsum Sebsibe Teni; Wondwessen Wale; Yihenew Ayalew; Betel Tesfaye (BMC, 2017)
Abstract Background Highly active antiretroviral therapy improves the longevity of patients living with HIV/AIDS. We conducted the study in order to assess health related quality of life of HIV/AIDS patients and the association of socio-demographic and disease related variables with health related quality of life. Methods Health facility based cross-sectional study among 400 HIV/AIDS patients taking highly active anti-retroviral therapy from Gondar University referral hospital was conducted. A pre-tested semi-structured questionnaire, which was adopted from World Health Organization Quality of life brief instrument, was used. The data were then analyzed using SPSS version 20 software for Windows. Results The majority of the respondents reported to to have a good physical health (15.55). The World Health Organization clinical stage was found to be significantly associated with all the domains of health related quality of life. The current acute illness condition of the respondents, however, did not show significant association with any of the domains of health related quality of life. Conclusions The six domains of health related quality of life were found to be moderate. The physical health and spirituality of the patients were relatively higher than their social relationship. Sex, age, educational status, residence and marital status showed significant association with at least one domain of health related quality of life.